DYNAMICS OF SUGARCANE AGRIBUSINESS IN EAST JAVA: HOW CAN PARTNERSHIPS ASSIST SMALL FARMERS IN ACCESSING THE MARKET? - Haryati, Novi; Rosyaadah, Nur Aini Irbah; Pratama, Rahmat Yoga; Herdianti, Dinda Febry; Aulia, Balqis Mufti; Nurirrozak, Muhamad Zahran (Agricultural Socio-Economics Journal, 2024)
In response to the growing demand for sugar that surpasses national production, enhancing sugar production capacity becomes imperative. This study, conducted in Watugede Village, Puncu District, Kediri Regency, East Java, from March to April 2019, explores the partnership dynamics between sugarcane farmers and sugar factories. Employing in-depth interviews and purposive sampling, the research assesses sugarcane farming feasibility, highlighting a favorable R/C ratio of 1.2 and a BEP unit of 37,837 kg, indicating the economic viability of sugarcane cultivation with revenues reaching Rp. 65,615,000. The agribusiness collaboration model identified is a subcontracting pattern between PG. Tjoekir and sugarcane farmers. Additionally, utilizing Porter's diamond model, the analysis reveals conducive factors supporting farmers' market access. These include favorable environmental conditions for sugarcane cultivation, a rising demand for sugar, and access to market information. In conclusion, fostering partnerships and improving farming practices showcase promising avenues for bolstering the sugar production sector.